Research of Design Method of Bevel Gear Tooth Profile based on Conical Involute - Hou Hongling; Xing Si; Shu Linsen (Jixie chuandong)
In order to making the tooth profile of bevel gear be close to its theoretical spherical involute,a design method of the tooth profile of bevel gear using conical involute is proposed,that is forming the involute tooth profile of bevel gears on the back cone surface directly. The conical involute can be expanded on plane,so the design and manufacturing of bevel gear become convenient. The mapping relation between plane involute of equivalent gear and conical involute are established by using the method of converse expansion,and the parameter equation of conical involute is derived in a rectangular coordinate system. The tooth profile of bevel gear is created by using the derived conical involute equation,and the parametric model of bevel gear is generated based on the conical involute eventually,the modeling accuracy is analyzed,the feasibility of the modeling method is verified.